Face extraction from non-uniform background and recognition in compressed domain - Tsapatsoulis, Nicolas; Doulamis, Nikolaos D.; Doulamis, Anastasios D.; Kollias, Stefanos D. (My University, 1998)
A complete face recognition system is proposed in this paper by introducing the concepts of foreground objects, which are currently used in the MPEG-4 standardization phase, to human identification. The system automatically detects and extracts the human face from the background, even if is not uniform, based on a combination of a retrainable neural network structure and the morphological size distribution technique. In order to combine face images of high quality and low computational complexity, the recognition stage is performed in the compressed domain. Thus, in contrast to existing recognition schemes, the face images are available in their original quality and not only in their transformed representation
Keywords: Pattern recognition systems; Computational complexity; Image compression; Neural networks; Face--Identification